An Exploration of Islamic-Based Institutional Management Models in Madura: Between Cultural Diversity and Organizational Effectiveness - Amar Ma'ruf Nahi Munkar; Ja’far Shodiq; Ahmad Walid (JUMPA : Jurnal Manajemen Pendidikan, 2023)
This research aims to explore the challenges and opportunities in implementing Islamic-based management models in educational institutions in Madura, which are rich in local culture. The main focus of this research is to integrate sharia principles with local customs and culture to create a more effective and harmonious managerial environment. The research methods used include in-depth interviews, participatory observations, and questionnaire surveys, which allow for the collection of qualitative and quantitative data. The research sample consisted of several Islamic educational institutions spread across Madura, with selection based on certain criteria such as the size of the institution and the involvement of local cultural figures. The results show that resistance to change and limited resources are the main obstacles to adopting an Islamic-based management model. However, opportunities such as community involvement in decision-making and innovation in managerial practices can be leveraged to overcome these barriers. The implications of this study show that a collaborative approach involving community leaders and other stakeholders can increase the effectiveness of educational institution management. Additionally, flexibility in policies and training programs that are sensitive to local contexts can increase employee acceptance and satisfaction. This research makes an important contribution to the development of a more adaptive and inclusive Islamic-based institutional management model, which can be applied in various cultural contexts. Further research is recommended to test this model in the long term and at different levels of educational institutions.